Graduate student supervision policies and procedures: A case study of issues and factors affecting graduate study - Donald, Janet G.; Saroyan, Alenoush; Denison, D. Brian (Canadian Journal of Higher Education, 1995)
This study was designed to identify salient issues in supervision across disciplines at a Canadian research university with a history of decentralized administration of graduate programs. Three sets of issues guided the inquiry: (a) the definition of supervision, (b) policies and procedures for supervision, and (c) the resources available for supervision. Although most departments reported having some form of policies and procedures, they did not tend to be explicitly stated or communicated. According to program directors, the two most important factors in the graduate supervision process were the supervisor's knowledge of the research field and his or her availability. There was considerable variability across faculties in the existence of policies and in the importance attached to different factors. Resources also varied greatly across disciplines. One conclusion of the study is that since the process of supervision is complex and occurs within a disciplinary context, much of the effort involved in enhancing the quality of graduate student supervision must be made at the department level. However, a comprehensive definition of graduate student supervision is needed to ensure that, where possible, there is common ground for graduate student supervision policy and practice.